Jagad Ageng and Jagad Alit In Traditional Kayons - Pandu Pramudita; Sarwanto Sarwanto; Soetarno Soetarno; Dendi Pratama (Pascasarjana Institut Seni Indonesia Surakarta, 2019)
Kayon is a shadow puppet character who symbolizes the world. In the Java world, there are two types of world concepts, namely the jagad ageng and the jagad alit. This study aims to examine the concepts of jagad ageng and jagad alit which are symbolized by the traditional kayons in purwa shadow puppets. The focus of this research study is to reveal the existence of Kayon Blumbangan and Kayon Gapuran as traditional kayons that have world essence, namely the jagad ageng and the jagad alit. Therefore, this study aims to reveal the existence and essence of Kayon Blumbangan and Kayon Gapuran as traditional kayons that store the concepts of jagad ageng and jagad alit. The method used in this research is iconography. Form theory which is divided into fields and ornament will become the main scalpel in analyzing the existence of Kayon Blumbangan and Kayon Gapuran. This research results that Kayon Blumbangan and Kayon Gapuran have the same shape structure with different widths of fields. The ornamental elements that form the kayon of the two traditional kayon are basically the same, namely forming four elements, including fire, water, wind, and earth. The four elements are the elements that make up the jagad ageng and the jagad alit. So, Kayon Blumbangan and Kayon Gapuran have a symbol of cosmological concepts regarding the concepts of jagad ageng and jagad alit.